A Bio‐inspired Nano‐pocket Spatial Structure for Targeting Uranyl Capture. Issue 11 (29th January 2020) - Yuan, Yihui; Feng, Shiwei; Feng, Lijuan; Yu, Qiuhan; Liu, Tingting; Wang, Ning
Abstract: Biology has evolved excellent spatial structures for high‐selectivity and high‐affinity capture of heavy metals. Inspired by the spatial structure of the superb‐uranyl binding protein SUP, we mimic the spatial structure of SUP in metal–organic frameworks (MOFs). The MOF UiO‐66‐3C4N fabricated by introducing 4‐aminoisophthalic acid into UiO‐66 shows high uranyl adsorption capacity both in simulated seawater and in natural seawater. In natural seawater, UiO‐66‐3C4N exhibits 17.03 times higher uranium extraction capacity than that of vanadium, indicating the high selectivity of the adsorbent. The EXAFS analysis and DFT calculation reveal that UiO‐66‐3C4N forms smaller nano‐pocket for uranyl capture than that of SUP protein, which can both restrict the entrance of the other interfering ions with larger size and reinforce the binding by increasing the coordination interaction, and therefore qualify the nano‐pocket with high affinity and high selectivity to uranyl. Abstract : Simply superb : Inspired by the spatial structure of the superb‐uranyl binding protein, a nano‐pocket is chemically mimicked in a metal–organic framework (MOF). The nano‐pocket exhibits targeted uranyl capture ability in natural seawater.